Google, Inc. : entrance into the Chinese market and government censorship - Harris, Brynn (SAGE Knowledge. Cases., 2017)
On January 25, 2006, the leading U.S. internet search engine Google, Inc. announced that it would be locating a new server inside China in order to provide Chinese citizens with their own portal, Google.cn. Locating the server inside China would allow for faster service than the Chinese version of the U.S. site was able to provide, and would give Google a greater chance at capturing China's estimated 111 million regular internet users. Locating the server in China also meant that the company had agreed to censor its search results in compliance with the laws of the Chinese government. The U.S. media and several human rights groups brought the issue to the publics attention, and Google's reputation and share price were severely damaged. The company now faces the challenge of rebuilding its reputation and balancing its idyllic corporate philosophy with the need to grow and capture market share.